Potential utilisation of wood residue in Kedah: A preliminary study - Mohd Shafie, Shafini; Othman, Zakirah; Hami, Norsiah (UUM College of Business, 2017)
Being an important resource-based industry in Malaysia, the wood industry plays a crucial role in the socioeconomic development of the country. In consequences, wood wastes generated exponentially increase annually.This paper views the current utilisation of wood waste production in the northern wood-based mills in Malaysia.The types of wood residue as well as the users of wood residue are identified.The result shows that 100% of wood residue are being used or sold for this population.However, the wood residue available in Kedah is able to potentially offer 0.005% of electricity generation in Malaysia.As a conclusion, this type of wood residue cannot create the opportunity for it to be used as fuel in electricity generation in the northern region of Malaysia, since the fuel supply is already limited and is being used for other purposes.